Evaluasi Kestabilan Sistem Penyangga pada Tambang Bawah Tanah Menggunakan Rock Mass Rating (RMR) pada Lubang Tambang Tambang Batubara BMK-30 CV. Bara Mitra Kencana Kec. Talawi, Kota Sawahlunto. - William Putra Simbolon; raimon kopa (Departemen Teknik Pertambangan FT UNP, 2023)
There are cracks and flaws in the wood that do not match the strength of the surrounding rock. There is a spacing between supports that exceeds the SOP of 2.5 m-2.8 m, which violates the company’s SOP of 1 m-1,5 m. The company does not have a buffer design appropriate for the rock load. In this study, the authors used quantitative research methodology. Quantitative research is research by obtaining data in the form of number or summarized qualitative data (Sugiyono, 2018:8). In conducting this research, there are primary data obtained directly from the field, namely the geometry of the opening hole, the dimensions of the wood support the condition of the discontinuous plane, the point load index value of the rock, the compressive strength value of the wood. A. the average value of saturated content weight of coal is 1.330 gr/cm3 and siltstone has a saturated content weight of 2.506 gr/cm3. B. the average value of point load index of coal is 0.246 MPa and siltstone has an average point load index of 0.837 gr/cm3. C. the results of converting PLI values to UCS, coa; has an average UCS value of 2,90MPa and siltstone has an average UCS value of 9.890 MPa. Based on the weighting of rock mass classes using the RMR system method, the results show that the right and left wall rock mass class, which is coal, has a value of 56 and includes class III rocks, and siltstone rocks are included in class II rocks as roofs. The standing time value of the roof opening hole section is 7,000 hours or for 291.67 days and the span with the provision of 4 meters of progress based on the specifiend RMR. From the wood specific gravity test, the average value of wood specific gravity is 0.51, which indicates that the wood used by CV. Bara Mitre Kencana is in class III. And for the bending strength value of wood of 623.75 kg/cm3. From the above calculations, the FK cap value is obtained after evaluating the distance between the supports. From the results of the above analysis, the FK value ≥1.5 is obtained with a support distance of 1.38 m.Keywords: Evaluation, Geometry, Faulting, Rock Weighting, Opening Geometry